Neurocognition Function of Patients With Bipolar Depression, Unipolar Depression, and Depression With Bipolarity - Lu, Zhe; Wang, Yingtan; Xun, Guanglei (Frontiers in Psychiatry, 2021)
Much evidence shows that some Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5)-defined unipolar depression (UD) with bipolarity manifests bipolar diathesis. Little is known about the cognitive profiles of patients with depression with bipolarity (DWB). The study aimed to investigate the differences in cognitive profiles among patients with bipolar depression (BD), major depressive disorder (namely, UD), and DWB. Drug-naïve patients with BD, UD, and DWB and healthy controls (HC) were recruited (30 cases in each group). Cognitive function was evaluated by THINC-it (THINC-intelligent tool), Wisconsin Card Sorting Test (WCST), and continuous performance test (CPT). For THINC-it, no significant differences of the Z-scores in both objective and subjective factors were found between the DWB group and BD group, but the Z-scores in the BD group were significantly lower than those in the UD group. For WCST, significant differences were found between the BD group and DWB group in the number of responses, categories completed, trails to completed first category, perseverative responses, and perseverative errors. All the indices of WCST in the DWB group were significantly worse than those in the UD group except for trails to completed first category and total number of response correct. For CPT, only scores of leakage responses and false responses in the four-digit number in the BD group and DWB group were significantly higher than those in the UD group; no significant difference was found between the BD group and DWB group. The results indicated that patients with DWB might perform differently from those with UD but similarly to those with BD with cognition impairment.